2021
DOI: 10.1093/infdis/jiab120
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Antibody Response to Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Post–COVID-19 Syndrome in Healthcare Workers

Abstract: It is currently unknown how Post-COVID-19 Syndrome (PCS) may affect those infected with SARS-CoV-2. This longitudinal study reports on healthcare staff who tested positive for SARS-CoV-2 between March-April 2020 and follows their antibody titres and symptomatology. Over half (n=21/38) had PCS at 7-8 months. There was no statistically significant difference between initial RT-PCR viral titres or serial antibody levels between those who did and did not develop PCS. This study highlights the relative commonality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 13 publications
(16 reference statements)
2
29
1
2
Order By: Relevance
“…Bashlyaeva Children’s Municipal Clinical Hospital N= 518 children (all previously hospitalized cases) Age Range: ≤18 Median Age: 10.4 (3–15.2) Sex (%F/%M): 52.1/47.9 Median 256 (223-271) days following discharge RT-PCR Subjective self-report via telephone surveyconducted by medical students 10.7% (53/518) reported fatigue scores on wellness scale for children with 2+ persistent symptoms significantly declined when compared to before COVID-19 onset (from 90 ( Augustin et al, 2021 , Cirulli et al, 2020 , Darley et al, 2021 , Ferrucci et al, 2021 , Kashif et al, 2021 , O’Keefe et al, 2021 , Peghin et al, 2021 , Shang et al, 2021 , Simani et al, 2021 , Stavem et al, 2021 , Xiong et al, 2021 , González-Hermosillo et al, 2021 , Petersen et al, 20212021 , Tawfik et al, 2021;18(3):em291. , Mei et al, 2021 , Evlice et al, 2021 ) to 70 ( Jacobson et al, 2021 , Johnsen et al, 2021 , Latronico et al, 2020 , Logue et al, 2021 , Menges et al, 2021 , Miskowiak et al, 2021 , Munblit et al, 2021 , Orrù et al, 2021 , Osmanov et al, 2021 , Pereira et al, 20212021 , Qu et al, 2021 , Rass et al, 2021;(ene.14803). , Savarraj et al, 2020 , Soldati et al, 2021 , Soraas et al, 2021 , Walle-Hansen et al, 2021 , Taboada et al, 2021 , Van Veenendaal et al, 2021 , Szende et al, 2014 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bashlyaeva Children’s Municipal Clinical Hospital N= 518 children (all previously hospitalized cases) Age Range: ≤18 Median Age: 10.4 (3–15.2) Sex (%F/%M): 52.1/47.9 Median 256 (223-271) days following discharge RT-PCR Subjective self-report via telephone surveyconducted by medical students 10.7% (53/518) reported fatigue scores on wellness scale for children with 2+ persistent symptoms significantly declined when compared to before COVID-19 onset (from 90 ( Augustin et al, 2021 , Cirulli et al, 2020 , Darley et al, 2021 , Ferrucci et al, 2021 , Kashif et al, 2021 , O’Keefe et al, 2021 , Peghin et al, 2021 , Shang et al, 2021 , Simani et al, 2021 , Stavem et al, 2021 , Xiong et al, 2021 , González-Hermosillo et al, 2021 , Petersen et al, 20212021 , Tawfik et al, 2021;18(3):em291. , Mei et al, 2021 , Evlice et al, 2021 ) to 70 ( Jacobson et al, 2021 , Johnsen et al, 2021 , Latronico et al, 2020 , Logue et al, 2021 , Menges et al, 2021 , Miskowiak et al, 2021 , Munblit et al, 2021 , Orrù et al, 2021 , Osmanov et al, 2021 , Pereira et al, 20212021 , Qu et al, 2021 , Rass et al, 2021;(ene.14803). , Savarraj et al, 2020 , Soldati et al, 2021 , Soraas et al, 2021 , Walle-Hansen et al, 2021 , Taboada et al, 2021 , Van Veenendaal et al, 2021 , Szende et al, 2014 , …”
Section: Resultsmentioning
confidence: 99%
“…Participants reported lower scores (poorer health state) at follow up (median 80 ( Miskowiak et al, 2021 , Munblit et al, 2021 , Orrù et al, 2021 , Osmanov et al, 2021 , Pereira et al, 20212021 , Qu et al, 2021 , Rass et al, 2021;(ene.14803). , Savarraj et al, 2020 , Soldati et al, 2021 , Soraas et al, 2021 , Walle-Hansen et al, 2021 , Taboada et al, 2021 , Van Veenendaal et al, 2021 , Szende et al, 2014 , Amin-Chowdhury et al, 2021 , Augustin et al, 2021 , Cirulli et al, 2020 , Darley et al, 2021 , Ferrucci et al, 2021 , Kashif et al, 2021 , O’Keefe et al, 2021 , Peghin et al, 2021 , Shang et al, 2021 , Simani et al, 2021 , Stavem et al, 2021 , Xiong et al, 2021 ) compared to pre-COVID (median 85 ( Qu et al, 2021 , Rass et al, 2021;(ene.14803).…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge concerning humoral immune response to SARS-CoV-2 and its relationship with post-COVID-19 syndrome is still incomplete ( 5 , 6 , 25 , 26 , 27 ). We found a significant association between growing titres of non-RBD SARS-CoV-2 antibodies after natural infection and post-COVID-19 syndrome in the prolonged follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The potential pathophysiological mechanisms are unknown and may encompass a complex interaction between the virus-specific cytopathic effects, the inflammatory damage, the allo- and autoimmune responses to the acute infection on the one hand, and the expected sequelae of post-critical illness due to organ and microvascular damage on the other ( 4 ). To date, there is still a gap on how natural immunity and hybrid immunity, which refer to the immune-strengthening effect of exposure to infection followed by vaccination, function in post-COVID 19 ( 5 , 6 , 7 ). A few studies available have suggested both a potential improvement and deterioration of post-COVID-19 symptoms after vaccination in previously infected patients and variable associations between humoral responses and post-COVID-19 syndrome after the natural infection ( 8 , 9 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in health care workers with the post-covide syndrome (PCS), one study found no significant relationship between RT-PCR and antibody level. The results showed that although some health care workers developed a severe and prolonged infection, the antibodies were not produced after infection (29). Thus, the frontline HCWs are at a higher risk of severe disease and mortality.…”
Section: Discussionmentioning
confidence: 95%